Literary and central productions Shalom Aleichem (Journal of the College of Basic Education, 2023)
The Jewish writer and writer Shalom Aleichem was born on the third of March 1859 in the city of Braslav.East of Kyiv (currently the capital of Ukraine), which was part of the Soviet Union, his real name is SolomonRenovitz and he called himself (Shalom Aleichem) as he used to sign all his productions under this name by which he became famous. What next...He spent his early years living in a small and cramped city, and this influenced his later productions.His father, Menachem Nahum Refinowitz, was a rabbi.